Correction: Transfection efficiencies of α-tocopherylated cationic gemini lipids with hydroxyethyl bearing headgroups under high serum conditions. Issue 8 (5th February 2019) - Maiti, Bappa; Kamra, Mohini; Karande, Anjali A.; Bhattacharya, Santanu
Abstract : Correction for 'Transfection efficiencies of α-tocopherylated cationic gemini lipids with hydroxyethyl bearing headgroups under high serum conditions' by Bappa Maiti et al., Org. Biomol. Chem., 2018, 16, 1983–1993.